Tending to destinations: Conceptualising tourism's transformative capacities. (September 2019) - Huijbens, Edward H; Jóhannesson, Gunnar Thór
This article is a theoretical contribution to inform scholarship on tourism destination development and dynamics. Our point of departure is the prevailing linear 'economic growth paradigm' animating tourism development discourse and practice. Through this discourse, people, landscapes, heritage and artefacts become valued as commodities and claims laid to tourism benefits emerge as objective, measurable facts. We contend that this discourse relies on an understanding of tourism resources and entrepreneurial activities as pure social constructs, which does not fully grasp the dynamics of emergent tourism realities and destinations' transformative capacities. We argue for alternative conceptualisations of tourism that equip tourism scholars with the conceptual tools to grasp the plurality of tourism futures. These involve 'vital materialism' built on a relational ontology foregrounding the creative life force that permeates us and all that surrounds us. We conclude with outlining the implications this approach has for the discussion of tourism destination development. We argue that these conceptual tools will lay the foundations for ethically sound tourism development in times of global uncertainties from the perspective of people, their commitments and aspirations and the environment.